2007
DOI: 10.1111/j.1742-4658.2007.06024.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘pair of sugar tongs’ site on the non‐catalytic domain C of barley α‐amylase participates in substrate binding and activity

Abstract: Some starch‐degrading enzymes accommodate carbohydrates at sites situated at a certain distance from the active site. In the crystal structure of barley α‐amylase 1, oligosaccharide is thus bound to the ‘sugar tongs’ site. This site on the non‐catalytic domain C in the C‐terminal part of the molecule contains a key residue, Tyr380, which has numerous contacts with the oligosaccharide. The mutant enzymes Y380A and Y380M failed to bind to β‐cyclodextrin‐Sepharose, a starch‐mimic resin used for α‐amylase affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 52 publications
6
90
0
1
Order By: Relevance
“…Subsequently mutagenesis in AMY1 (Søgaard et al 1993) and crystallography of AMY2 (Nielsen et al, manuscript in preparation). Also in human salivary α-amylase four Bozonnet et al (2007). b Fukuda et al (2005); M6 = A42P AMY2.…”
Section: Impact Of Secondary Binding Sites On Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently mutagenesis in AMY1 (Søgaard et al 1993) and crystallography of AMY2 (Nielsen et al, manuscript in preparation). Also in human salivary α-amylase four Bozonnet et al (2007). b Fukuda et al (2005); M6 = A42P AMY2.…”
Section: Impact Of Secondary Binding Sites On Functionmentioning
confidence: 99%
“…6) that by mutational analysis was demonstrated to be important for oligosaccharide binding. Thus K D for the starch mimic β-CD was determined by surface plasmon resonance analysis to augment from 0.20 mM for wild-type to 1.4 mM for Y380A AMY1 (Table 1; Bozonnet et al 2007). The Y380A AMY1 mutant had a 13-fold reduced affinity and about 90% reduced catalytic efficiency towards starch granules as compared to the wild-type enzyme.…”
Section: Impact Of Secondary Binding Sites On Functionmentioning
confidence: 99%
“…However, characterization of separate binding events at different binding sites (AS and SBSs) in these glycoside hydrolases is challenging. Surface plasmon resonance (SPR) experiments showed that substrate binding affinity changed upon sitedirected mutagenesis of the two SBSs in barley α-amylase [2,3]. Nuclear magnetic resonance (NMR)-monitored titration experiments demonstrated that binding of xylooligo-saccharides to the Bacillus circulans xylanase AS and SBS occurs independently, whereas binding of longer chains to both sites occurs cooperatively [4].…”
mentioning
confidence: 99%
“…In the high pI isozyme AMY2, despite the presence of the corresponding tyrosine (Tyr378), the serine was replaced by a proline (Pro376) that contributes to a more restrained loop and consequently may prevent the binding [10]. Of the four α-amylase isoforms from wheat, it is very probable that isoforms TaAMY2 and TaAMY3 can undertake this "sugar-tongs"-like surface binding activity, whereas for the isoforms TaAMY1 and TaAMY4 the binding would be hindered due to serine to proline replacement (Figure 3d,e), as observed in the high pI isozyme of barley α-amylase [50].…”
Section: Taamy Family Protein Structuresmentioning
confidence: 99%
“…(b) Structural models of representatives of four wheat α-amylase families shown in a similar orientation as that of the barley α-amylase structure. All four models were obtained at the fold recognition server Phyre-2 [41] using the low pI α-amylase isozyme AMY1 (PDB code: 2QPU; [50]) as the best template in each case at the confidence equal to 100, sequence identity no lower than 64% and at least 91% alignment coverage. (c-e) Structural overlay of domain C emphasizing the 'pair of sugar tongs' site identified in the barley α-amylase AMY1 and corresponding residues in the models of four wheat α-amylases.…”
Section: Evolutionary Relationshipsmentioning
confidence: 99%